2012
DOI: 10.1371/journal.pone.0050968
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Fatty Acid Binding Protein (FABP) Anandamide Transporters – A Novel Strategy for Development of Anti-Inflammatory and Anti-Nociceptive Drugs

Abstract: Fatty acid binding proteins (FABPs), in particular FABP5 and FABP7, have recently been identified by us as intracellular transporters for the endocannabinoid anandamide (AEA). Furthermore, animal studies by others have shown that elevated levels of endocannabinoids resulted in beneficial pharmacological effects on stress, pain and inflammation and also ameliorate the effects of drug withdrawal. Based on these observations, we hypothesized that FABP5 and FABP7 would provide excellent pharmacological targets. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
189
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(208 citation statements)
references
References 28 publications
8
189
2
Order By: Relevance
“…In agreement with previous studies, CBD inhibited both rat and mouse but not human FAAH (Fig. 3D), suggesting a species specificity that may underlie these effects (14,44). To further investigate this species specificity, we employed site-directed mutagenesis to interconvert key residues within the active site of human FAAH to the homologous residues found in rat FAAH.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In agreement with previous studies, CBD inhibited both rat and mouse but not human FAAH (Fig. 3D), suggesting a species specificity that may underlie these effects (14,44). To further investigate this species specificity, we employed site-directed mutagenesis to interconvert key residues within the active site of human FAAH to the homologous residues found in rat FAAH.…”
Section: Resultssupporting
confidence: 88%
“…HeLa cells are a suitable cell type to examine interactions of exogenous cannabinoids with FABPs and their effects upon endocannabinoid transport because these cells conveniently express a single FABP subtype, FABP5 (12,14), AEA uptake is coupled to its breakdown by FAAH (42,43). Therefore, HeLa cells, which lack FAAH (44), were transfected with human FAAH and AEA uptake was subsequently examined.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a biphasic expression of FABP5 was observed in this study, with an initial down-regulation as part of immune response initiation, followed by recovery of expression levels to aid attenuation of the inflammatory response, possibly in conjunction with increased expression of PPAR (39). A specific inhibitor of FABP5, namely AM404, was used to show that FABP5 enhances the action of Nacylethanolamine, a PPAR agonist, by increasing its uptake and nuclear translocation in Hela cells (38). Thus, several studies have shown that FABP5 interacts with the PPAR class of nuclear receptors and we speculate that these interactions are cell-and tissue-dependent, while probably also driven by substrate supply and the metabolic requirements of the specific cells.…”
Section: Fabp5 (Epithelial Fabp Keratinocyte Fabp Efabp Kfabp)mentioning
confidence: 67%
“…FABP5 has been found at detectable levels in adipocytes, macrophages, endothelial cells, lung epithelium, neural tissues and breast tumour (1)(37) (38). The role of FABPs in regulating cell proliferation is also seen with FABP5, where levels are up-regulated in breast tumours, promoting proliferation and metastatis in cultured cells, most likely through interactions with PPAR (37).…”
Section: Fabp5 (Epithelial Fabp Keratinocyte Fabp Efabp Kfabp)mentioning
confidence: 99%
“…peroxisome proliferator-activated receptor, exhibiting properties of anti-inflammation and antioxidative stress (Berger et al, 2012;Gally et al, 2013). Overexpression of FABP5 in adipose tissue results in increased lipolysis, decreased fat mass, and potentiated insulin resistance (Hertzel et al, 2006).…”
Section: Crosstalk Of Nrf2 and Estrogen Signaling In Lipid Metabolismmentioning
confidence: 99%